Lost in transition : the dark side of emerging adulthood - Smith, Christian, 1960-; Hojara, Kari M.; Davidson, Hilary; Herzog, Patricia Snell (New York : Oxford University Press, 2011)
In Lost in Transition, Christian Smith and his collaborators draw on 230 in-depth interviews with a broad cross-section of emerging adults (ages 18-23) to investigate the difficulties young people face today, the underlying causes of those difficulties, and the consequences both for individuals and for American society as a whole. --from publisher description
Morality adrift -- Captive to consumerism -- Intoxication's "fake feeling of happiness" -- The shadow side of sexual liberation -- Civic and political disengagement.
Includes bibliographical references and index.
Keywords: Young adults -- United States -- Attitudes; Young adults -- United States -- Social life and customs -- 21st century; Young adults -- United States -- Conduct of life